Construction of a Polarization Multiphoton Controlled One‐Photon Unitary Gate Assisted by the Spatial and Temporal Degrees of Freedom. Issue 9 (9th July 2019) - Xiu, Xiao‐Ming; Geng, Xue; Wang, Sen‐Lin; Cui, Cen; Li, Qing‐Yang; Ji, Yan‐Qiang; Dong, Li
Abstract: In order to fulfill quantum information processing tasks such as quantum computation and scalable quantum networks, quantum logic gates are indispensable parts. A multiqubit logic gate can efficiently reduce the cost of physical resources and complicated operations that are necessary in the combination of fewer‐qubit (e.g., two‐qubit) logic gates to fulfill the same tasks. However, the construction of multiphoton quantum logic gates is a large challenge. Assisted by spatial and temporal degrees of freedom, a polarization multiphoton controlled one‐photon unitary gate is proposed, which can be realized with three processes including the control‐path process based on weak cross‐Kerr nonlinearities, the unitary transformation process, and the output process. In the control‐path process, the control‐path modules are applied, where the entanglement between polarization, spatial and temporal degrees of freedom is generated by beam splitters, time delayers, and nonlinear interaction in cross‐Kerr media. The scheme presented here, assisted by spatial and temporal degrees of freedom reduces the experimental complexity of the schemes assisted by only spatial degree of freedom. Moreover, it will also be a useful reference in optimally constructing multiqubit quantum logic gates with other multiple degrees of freedom in many physical systems. Abstract : Based on the spatial and temporal degrees of freedom, a construction scheme of a nearly deterministic polarization multiphoton controlled one‐photon unitary gate with a simple construction circuit and available measurement techniques and operations is proposed, which can be realized with three processes including the control‐path process based on weak cross‐Kerr nonlinearities, the unitary transformation process, and the output process.